Perception of English lexical stress: some insights for English pronunciation lessons for Iraqi ESL learners - Al-Thalab, Hasan Shaban Ali; Yap, Ngee Thai; Nimehchisalem, Vahid; Rafik-Galea, Shameem (Universiti Putra Malaysia Press, 2018)
One basic factor that influences perception of lexical stress is the number of syllables found in the word and the syllable weight as lexical stress is often assigned to heavy syllables. However, what is considered as a heavy syllable is language specific and this causes problems when two different language systems interact as in the case of second language learning. This paper reports the findings of a study that examined the identification of lexical stress by ESL learners to identify specific syllable structure in English that may pose difficulty to Iraqi learners of English. The results showed that Iraqi Arabic subjects performed poorer in trisyllabic words compared to disyllabic words. High error rates were obtained when the words had two superheavy syllables or two or more equally heavy syllable. Words with long vowels and final consonant clusters, considered as superheavy syllables, often attract stress in Iraqi Arabic but the distribution of such syllables is often more restricted in Arabic. However this is not the case in English and this difference in the distribution of heavy and superheavy syllables influences perception of lexical stress among Iraqi ESL learners. The results show that Iraqi Arabic learners' ability to correctly identify lexical stress is influenced by their native language experience, in particular the L1 stress patterns and strong dependence on syllable structure in lexical stress assignment in Iraqi Arabic.